+0  
 
0
215
1
avatar+644 

Let x = 2012(a - b), y = 2012(b - c) and z = 2012(c - a) where a,b,c are real numbers, and assume xy + yz + zx  ≠ 0. Compute {x^2 + y^2 + z^2}/{xy + yz + zx}

waffles  Jan 25, 2018
 #1
avatar+87604 
+1

x^2  =  2012^2(a - b)^2 

y^2 =  2012^2 (b - c)^2

z^2 =  2012^2 (c - a)^2

xy = 2012^2(a - b) (b - c)

yz  = 2012^2 (b -c) (c - a)

xz =  2012^2 (a - b)(c - a)

 

So

 

 {x^2 + y^2 + z^2}/{xy + yz + zx}  =

 

[  2012^2 [  ( a- b)^2  + (b - c)^2 + ( c - a)^2 ] ]/ [ 2012^2 [ (a-b)(b -c) +(b -c)(c - a) +(a -b) (c-a)] ]

 

[ ( a - b)^2 + (b - c)^2  + (c - a)^2) ]  /  [  (b - c) ( a - b + c - a)  + (a - b)(c - a) ]

 

[ ( a - b)^2 + (b  - c)^2 + (c - a)^2 ]  /  [  (b -c) (c - b) + ( a - b)(c - a) ] 

 

[  a^2 - 2ab + b^2 + b^2 - 2bc + c^2 + c^2 - 2ac + a^2]  / [  - ( b - c)^2  + (a - b)(c - a)]

 

[  2 [ a^2 + b^2 + c^2]  - 2 [ ab + bc + ac ] ]/ [ -b^2 + 2bc - c^2   + ac - bc - a^2 + ab ]

 

[ 2 [ a^2 + b^2 + c^2] - 2 [ ab + bc + ac] ] / [ - [ a^2 + b^2 + c^2]  + [ ab + bc + ac] ]

 

[ 2  [ a^2 + b^2 + c^2 - ab - bc - ac ] ]  /  [ - 1 [ a^2 + b^2 + c^2 - ab + bc + ac ] ]

 

=

 

2 / -1  =

 

-2

 

 

cool cool cool

CPhill  Jan 25, 2018

18 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.